A TACTICAL FOURTH AMENDMENT - Garrett, Brandon; Stoughton, Seth (Virginia law review, 2017)
What rules regulate when police can kill? As ongoing public controversy over high-profile police killings drives home, the civil, criminal, and administrative rules governing police use of force all remain deeply contested. Members of the public may assume that police rules and procedures provide detailed direction for when officers can use deadly force. However, many agencies train officers to respond to threats according to a force "continuum" that does not provide hard-edged rules for when or how police can use force or deadly force. Nor, as recent cases have illustrated, does a criminal prosecution under state law readily lend itself to defining appropriate police uses of force. People might assume that the U.S. Constitution protects citizens against completely unjustified uses of deadly force. They would be wrong to expect clear constitutional rules either, particularly in the wake of the U.S. Supreme Court's ruling in Graham v. Connor. Can the Fourth Amendment doctrine be revitalized? This Article begins by excavating key lessons from an earlier moment in time when the Supreme Court did, after careful consideration, adopt in Tennessee v. Garner constitutional rules based on the then-new field of police tactics. Today, where can we turn to develop sound guidance for police use of force? Police tactics have advanced considerably in the decades since, as has policing technology. We conducted an empirical analysis of the force policies of the fifty largest policing agencies in the United States, and found that many agencies lacked guidance on key subjects, such as the need to provide verbal warnings before using force. However, we identify a consistent approach among prominent agencies that adopt detailed policies incorporating tactical methods to de-escalate and minimize the need to use force, some in response to Department of Justice consent decrees. We also find real promise in lower court rulings that rely on tactical research and policy when assessing liability of police. This Article develops a theory of police use of force grounded in the growing body of police-tactics research designed to accomplish law enforcement goals while protecting the lives of officers and citizens. The courts, law enforcement, and the public all desperately require a revitalized constitutional standard regulating police use of force: It is time that we adopt a tactical Fourth Amendment.